Contemporary screen time modalities and disruptive behavior disorders in children: a prospective cohort study. (26th July 2022) - Nagata, Jason M.; Chu, Jonathan; Ganson, Kyle T.; Murray, Stuart B.; Iyer, Puja; Gabriel, Kelley Pettee; Garber, Andrea K.; Bibbins‐Domingo, Kirsten; Baker, Fiona C.
Abstract : Background: Cross‐sectional studies have demonstrated associations between screen time and disruptive behavior disorders (conduct disorder and oppositional defiant disorder); however, prospective associations remain unknown. This study's objective was to determine the prospective associations of contemporary screen time modalities with conduct and oppositional defiant disorder in a national cohort of 9–11‐year‐old children. Methods: We analyzed data from the Adolescent Brain Cognitive Development (ABCD) Study ( N  = 11, 875). Modified Poisson regression analyses were conducted to estimate the associations between baseline child‐reported screen time (total and by modality) and parent‐reported conduct or oppositional defiant disorder based on the Kiddie Schedule for Affective Disorders and Schizophrenia (KSADS‐5) at 1‐year follow‐up, adjusting for potential confounders. Results: Participants reported an average of 4 hr of total screen time per day at baseline. Each hour of total screen time per day was prospectively associated with a 7% higher prevalence of conduct disorder (95% CI 1.03–1.11) and a 5% higher prevalence of oppositional defiant disorder (95% CI 1.03–1.08) at 1‐year follow‐up. Each hour of social media per day was associated with a 62% higher prevalence of conduct disorder (95% CI 1.39–1.87). Each hour of video chat (prevalence ratio [PR] 1.21, 95% CI 1.06–1.37), texting (PR 1.19, 95% CI 1.07–1.33), television/movies (PR 1.17, 95% CI 1.10–1.25), and video games (PR 1.14, 95% CI 1.07–1.21) per day was associated with a higher prevalence of the oppositional defiant disorder. When examining thresholds, exposure to >4 hr of total screen time per day was associated with a higher prevalence of conduct disorder (69%) and oppositional defiant disorder (46%). Conclusions: Higher screen time was prospectively associated with a higher prevalence of new‐onset disruptive behavior disorders. The strongest association was between social media and conduct disorder, indicating that future research and interventions may focus on social media platforms to prevent conduct disorder.